Perilaku Konsumtif Sebagai Sebuah Gaya Hidup: Studi Komunitas Lari LibuRUN di Kota Pekanbaru - Abdul Hafizh; Hesti Asriwandari; Achmad Hidir (Jayapangus Press, 2022)
The LibuRUN group is a running community that is highly famous in Riau, notably in the city of Pekanbaru. The objective of founding the LibuRUN running community is to push for the residents of Pekanbaru city to live a healthy life. This research intends to examine the consumptive and hedonic behavior of members of the LibuRUN running community. The research approach utilized in this study is descriptive qualitative, the source of the data comprises of primary and secondary data. The findings indicated that consumer behavior among LibuRUN members was impacted by their surroundings and their personal wishes, and LibuRUN hedonic lifestyle was conduct that was regarded normal and hedonic behavior was also typical. Behavior arises because of behaviors that exist among the community and people themselves.